Massive pulmonary embolism in a young boy with T-cell leukaemia - Beck, O.; Martin, C.; Alt, F.; Wingerter, A.; Staatz, G.; Schinzel, H.; Faber, J. (Hämostaseologie, 2014)
Acute pulmonary embolism (PE) is a serious complication in association with malignant diseases. We describe the successful treatment of PE applying a systemic thrombolytic therapy in a 4-year-old boy with acute lymphoblastic leukaemia.The thrombolytic therapy with recombinant tissue plasminogen activator (rtPA) 0.1 mg/ kg bodyweight per hour for six hours was continued for six days without important side effects. In particular no bleeding complications were observed. Computed tomography with contrast revealed a remarkable regression of the central PE. Without further delays the chemotherapy was resumed.
Keywords: Pulmonary embolism; leukaemia; recombinant tissue plasminogen activator; rtPA; children